Seasonality of climate elements and their influence on litter in a successional forest in eastern Amazon - Machado-Lima, Juliana Cristina (2021)
The production and decomposition of litter is important in the functioning and dynamic of a forest ecosystem, associating climatological variables to biomass. With that, the litter stock was investigated due to the seasonality of the climate in a successional forest in eastern Amazon. The study was conducted in a successional forest, in the metropolitan region of Belém (RMB), Pará. In the ecosystem, a random sampling was performed in three transects located along the perpendicular of the 50m border line. The analysis of the effect of the seasonality of the elements of the climate on the litter physical properties (volume, thickness, density and dry mass) and carbon content were carried out using the t Student test and ANOVA of the F test at 5% significance level. Precipitation (495.2 ± 125mm and 109.8 ± 60mm) and relative humidity (89.0 ± 1.7% and 79.6 ± 2.8%) showed a statistical difference in seasonality (p<0.05), different from the temperature (27.1 ± 0.2ºC and 27.6 ± 0.3ºC), there was no difference. The litter variables were not influenced by the seasonality of the elements of the climate and did not differ statistically between the rainy and less rainy periods, respectively: amount of accumulated litter (16.46 ± 4.17 Mg.ha-1 and 13.91 ± 7.61 Mg.ha-1), litter carbon stock (7.9 ± 2, 0 Mg.ha-1 and 6.6 ± 3.61 Mg.ha-1), volume (26.21 ± 0.92cm3 and 24.88 ± 0.92 cm3), thickness (4.19 ± 0.92cm and 3.99 ± 0.95cm) and density (0.041 ± 0.92g/cm3 and 0.034 ± 0.92 g/cm3). The seasonality of the elements of the climate did not show considerable variation to the point of altering the litter physical properties and carbon content.